223Ra Dichloride Bone-Targeted Therapy in a Case of Metastatic Salivary Duct Carcinoma. (May 2017) - Manfredi, Matteo; Airoldi, Mario; Tucci, Marcello; Buttigliero, Consuelo; Parente, Antonella; Angusti, Tiziana
Abstract : Abstract: Salivary duct carcinoma (SDC) is a rare malignancy, frequently overexpressing androgen receptor (AR). Therefore, similar to AR-positive prostate cancer (PCa), AR-positive SDC patients benefit from androgen deprivation therapy and, after progression on ADT, might take advantage of 223 Ra dichloride, a radiopharmaceutical approved for the treatment of castration-resistant PCa with symptomatic bone disease. We report the case of a 75-year-old man with castration-resistant SDC and osteoblastic bone metastases who, after 223 Ra treatment, achieved adequate control of bone pain and bone lesion reduction with minor side effects. Evaluation of this strategy in other patients with similar characteristics is warranted.